Engaging students as partners in learning and teaching : a guide for faculty - Cook-Sather, Alison, 1964-; Bovill, Catherine; Felten, Peter (San Francisco : Jossey-Bass, 2014)
'The book is designed to offer both a theoretical grounding and practical guidelines and advice--from faculty, students, and coordinators/directors of teaching and learning centers--on how to develop student-faculty partnerships focused on affirming and improving teaching and learning in higher education. This is a why-to and a how-to book, and it provides those interested in trying out their own version of student-faculty partnerships with theory and evidence that supports such efforts, various models of how to go about creating and supporting such partnerships, and advice from a wide-range of experts, on the one hand, and faculty and students who have tried this approach, on the other hand. That balance--of theory, step-by-step guidelines, expert advice, and practitioner experience - will provide those interested with a wide range of perspectives and possibilities on how to build student-faculty partnerships and various levels of guidance. The book will include helpful responses to a range of questions that we have been asked by academic staff from different institutions, disciplines, and levels of experience. These responses will attempt to help faculty overcome some of the perceived barriers to student-faculty partnerships and suggest a range of possible levels of partnership that might be appropriate in different circumstances'--
What are student-faculty partnerships? : Our guiding principles and definition -- Preliminary questions about student-faculty partnerships -- Partnerships with students : Examples from individual faculty -- Program-level approaches to student-faculty partnerships -- Outcomes of student-faculty partnerships: Support from research literature and outcomes for faculty and students -- The challenges of student-faculty partnerships -- Practical strategies for developing student-faculty partnerships -- Further questions about student-faculty partnerships -- Assessing processes and outcomes of student-faculty partnerships -- Next steps. . .toward a partnership movement?
Includes bibliographical references and index.
Keywords: College teaching; Teacher-student relationships; Learning, Psychology of